Hypertension is associated with increased mortality in patients with ischaemic heart disease after revascularization with percutaneous coronary intervention – a report from SCAAR*. (4th May 2017) - Saluveer, Ott; Redfors, Björn; Angerås, Oskar; Dworeck, Christian; Haraldsson, Inger; Ljungman, Charlotta; Petursson, Petur; Odenstedt, Jacob; Ioanes, Dan; Lundgren, Peter; Völz, Sebastian; Råmunddal, Truls; et al.
Abstract: Background: The prognostic role of hypertension on long-term survival after percutaneous coronary intervention (PCI) is limited and inconsistent. We hypothesize that hypertension increases long-term mortality after PCI. Methods: We analyzed data from SCAAR (Swedish Coronary Angiography and Angioplasty Registry) for all consecutive patients admitted coronary care units in Sweden between January 1995 and May 2013 and who underwent PCI due to ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI)/unstable angina (UA) or stable angina pectoris. We used Cox proportional-hazards regression for statistical modelling on complete-case data as well as on imputed data sets. We used interaction test to evaluate possible effect-modulation of hypertension on risk estimates in several pre-specified subgroups: age categories, gender, diabetes, smoking and indication for PCI (STEMI, NSTEMI/UA and stable angina). Results: During the study period, 175, 892 consecutive patients underwent coronary angiography due to STEMI, NSTEMI/UA or stable angina. 78, 100 (44%) of these had hypertension. Median follow-up was 5.5 years. After adjustment for differences in patient's characteristics, hypertension was associated with increased risk for mortality (HR 1.12, 95% CI 1.09–1.15, p < .001). In subgroup analysis, risk was highest in patients less than 65 years, in smokers and in patients with STEMI. The risk was lowest in patients with stable angina ( p < .001 for interaction test). Conclusion: Hypertension is associated with higher mortality in patients with STEMI, NSTEMI/UA or stable angina who are treated with PCI.